Spatial distribution, morphological characteristics, and risk assessment of microplastics in the beach sediments of Odisha Coast, India - Shaji, Sheha; Rao, Y. R. Satyaji; Sundaram, Baranidharan (Frontiers in Water, 2026)
Despite the growing recognition of microplastic (MP) pollution in coastal environments, studies on their spatial distribution along the eastern coastline of India remain limited. The present study examined the prevalence and characteristics of microplastics (MPs) in beach sediments along the Odisha coast, India. Samples were collected from 34 distinct beach locations along the coastline, providing the most spatially extensive baseline dataset currently available for MPs contamination in the region. Additionally, the study evaluated associated environmental risks using multiple risk indices. The average abundance was 948±268 particles/kg. The results revealed spatial variability in MPs abundance across Odisha coast wherein the central coastal region exhibited highest mean concentration, meanwhile the southern region had lowest mean concentration, but the highest variability. The majority particles size ranged from 100-2000µm, with fibres (98.9%) being the predominant form followed by fragments and films. Major polymer types identified by micro-Raman spectroscopy were polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE) and polyester (PES). Polymer-induced hazard index (PHI) placed the sampling locations in risk categories IV and V, while pollution load index (PLIodisha-2.59) deemed the coast polluted. The potential ecological risk index (PERIodisha- 93206.5) indicated extreme danger. Meanwhile, in 32 places, RQ>1 indicated threat to the ecosystem. As one of the first large scale assessments of MPs along the Odisha coast, this study not only fills a critical regional data gap but also contributes towards the expanding global body of evidence, highlighting urgent policy and conservation responses to MPs pollution.